Quantum optics - Garrison, J. C. (John Carson), 1935-; Chiao, Raymond Y. (Oxford : Oxford University Press, 2008)
This text develops the theoretical and experimental basis of quantum optics, i.e. the interaction of individual particles of light (photons) with matter, starting from elementary quantum theory. The self-contained exposition will be useful to graduate students in physics, engineering, chemistry, and senior undergraduates in physics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Quantum optics